Biosynthesis and characterization of magnesium oxide and manganese dioxide nanoparticles using Matricaria chamomilla L. extract and its inhibitory effect on Acidovorax oryzae strain RS-2 - Solabomi Olaitan Ogunyemi; Feng Zhang; Yasmine Abdallah; Muchen Zhang; Yanli Wang; Guochang Sun; Wen Qiu; Bin Li (Artificial Cells, Nanomedicine, and Biotechnology)
Bacterial brown stripe (BBS) is one of the most economically important diseases of rice caused by Acidovorax oryzae (Ao). In order to ensure food security and safe consumption, the use of non-chemical approach is necessary. In this study, MgO and MnO2 were synthesized using chamomile flower extract. The synthesized MgO and MnO2 nanoparticles were characterized by UV–Visible spectroscopy, Fourier transform infrared spectroscopy, X-ray diffraction, transmission/scanning electron microscopy. The sizes were 18.2 and 16.5 nm for MgO and MnO2 nanoparticles, respectively. The MgO and MnO2 nanoparticles reduced the growth of Ao strain RS-2 by 62.9 and 71.3%, respectively. Also, the biofilm formation and swimming motility were significantly reduced compared to the control. The antibacterial mechanisms of MgO and MnO2 nanoparticles against RS-2 reveals that MgO and MnO2 nanoparticles penetrated the cells and destroyed the cell membrane leading to leakage of cytoplasmic content. Also, the flow cytometry observation reveals that the apoptotic cell ratio of RS-2 increased from 0.97% to 99.52 and 99.94% when treated with MgO and MnO2 nanoparticles, respectively. Altogether, the results suggest that the synthesized MgO and MnO2 nanoparticles could serve as an alternative approach method for the management of BBS.